Ultrasound-guided percutaneous release procedures in the transverse carpal ligament by acupotomy: A cadaveric study - Zhou, Qiaoyin; Shen, Yifeng; Zhu, Xinyue; Sun, Xiaojie; Qiu, Zuyun; Li, Shiliang; Zhang, Weiguang (Frontiers in Surgery, 2023)
Objective: This study aimed to determine the safety and accuracy of ultrasound-guided acupotomy percutaneous loosening of the transverse carpal ligament. Methods: The 100 upper limb specimens were equally divided into the ultrasound-guided acupotomy group (U) and the nonultrasound-guided acupotomy group (N). For the U group, we simulated ultrasound-guided acupotomy loosening of the transverse carpal ligament in a human specimen, and for the N group, we performed the loosening of the transverse carpal ligament through the same approach under nonultrasound-guided conditions. The safety and accuracy of the two methods were compared through measurement. Results: According to the measurement, the ultrasound-guided acupotomy technology had high safety and accuracy. Conclusion: In this study, we designed a new method for cutting the transverse carpal ligament under ultrasound guidance, which is different from surgery. These results indicate that this is a safe and accurate method of interventional treatment of carpal tunnel syndrome.